Morphometric Characteristics of Galekan Cattle Breed Base on Principle Component Analysis (PCA) - Kuswati Kuswati; Muhammad Irvan Ali; Rini Dwi Wahyuni (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
This study obtained morphometric information on Galekan cattle and compared phenotypic characteristics of Galekan cattle with local breed based on previous studies. This research was a case study with purposive sampling using the snowball sampling technique. The material used was 60 cattle of Galekan cattle which were kept in the Technical Unit (UPT) at Dongko and Panggul Sub Districts. The variables observed included qualitative characteristics and quantitative characteristics of morphometric components and body weight. T2-Hotelling test, descriptive statistics, and principal component analysis are used for quantitative data. The results showed that the qualitative characteristics of Galekan cattle were dominated by light brown body color with smear body color border, black backline, black vulva, black tail tip, face color as same as dominant body color, black muzzle, black upper and lower lips, smear white eye area, dark eye circles, black eyelashes, and black ear lines. The characteristics of the body shape of Galekan cattle have upward horns, no hump, and thin dewlap. The results of the T2-Hotelling analysis in UPT showed a significant difference (p <0.05) compared to other cattle in Dongko and Panggul Sub Districts. Principal component analysis (PCA) of Galekan cattle can be characterized by body weight, chest girth, depth chest, Ossa vertebrae lumbales, Ossa metatarsal, and Ossa vertebrae thoracicae.